Key technologies of 6G mobile network - Haijun ZHANG; Anqi CHEN; Yabo LI; Keping LONG (Tongxin xuebao)
The development and social needs of mobile communication networks were firstly introduced.Then four key technologies of 6G network were respectively introduced from the perspectives of communication spectrum, coverage dimension, communication empowerment, and new paradigm, namely terahertz (THz) communication, space-air-ground-sea integration network, artificial intelligence (AI), and semantic communication.The related researches of the four key technologies in recent years were analyzed, and some typical application scenarios, coverage scheme, technique principles, etc., were summarized.Finally, based on the summary, main problems of the four technologies were proposed for the future development.Besides, other candidate technologies of 6G network, including integrated sensing and communication, reconfigurable intelligence surface and new materials, blockchain, digital twin, and deterministic network technology, etc., were briefly discussed in the conclusion part.